Identification of Abnormal Biliary Anatomy Utilizing Real-Time Near-Infrared Cholangiography: A Report of Two Cases - Joseph Bozzay; Diego Vicente; Elliot M. Jessie; Carlos J. Rodriguez (Case Reports in Gastrointestinal Medicine)
Biliary duct anomalies are commonly encountered during laparoscopic cholecystectomy. Advancements in the field of surgery allow for enhanced intraoperative detection of these abnormalities. Fluorophore injection and near-infrared (NIR) imaging can provide real-time intraoperative anatomic feedback without intraoperative delays and ionizing radiation. This report details two cases where the PINPOINT Endoscopic Fluorescence Imaging System (NOVADAQ, Ontario, Canada) was used to identify anomalies of the biliary tree and guide operative decision-making.